Valor nutritivo de fenos de moringa (moringa oleifera lam) com diferentes idades de corte - Melo, Samara Suênya Nogueira Serafim de (2012)
This study was conducted to evaluate the consumption and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), total carbohydrates (TC), non-fiber carbohydrates (NFC) and neutral detergent fiber (NDF) in sheep fed hay moringa (Moringa oleifera Lam) obtained with four cutting ages (28, 35, 42 and 49 days). We used 20 females Morada Nova breed, with 20kg of live weight, distributed in a completely randomized design and maintained in metabolism cages. There was a negative linear effect of age of cutting on DM intake, with an estimated maximum consumption of 0.67 kg / day for the hay produced at 28 days of cutting. It was also observed linear behavior, with an estimated maximum consumption 172g/dia, 0.36 kg / day; 18g/dia, at 35, 42 and 49 days old, for CP, OM and EE, respectively. For NDF, quadratic effect was found with advancing maturity of the plant. The apparent digestibility of DM, CP, OM and TC linearly decreased with advancing age of cutting hay Moringa oleifera. It was concluded that the hay Moringa oleifera showed better nutritional value after 28 days of cutting